'People listen more to what actors say': A qualitative study of tuberculosis-related knowledge, behaviours, stigma, and potential interventions in Puducherry, India. Issue 11 (2nd November 2022) - Sabin, Lora L; Thulasingam, Mahalakshmy; Carwile, Madeline; Babu, Senbagavalli Prakash; Knudsen, Selby; Dong, Lijia; Stephens, Jessie; Fernandes, Priyanka; Cintron, Chelsie; Horsburgh, C Robert; Salgame, Padmini; Ellner, Jerrold J; et al.
ABSTRACT: India has made substantial advancements in reducing the burden of tuberculosis (TB), but persons living with active TB (PLWATB) still face myriad challenges in seeking and receiving care, including TB-related stigma. To meet the END TB targets, it is critical that PLWATB engage in care and are able to adhere to treatment. This qualitative study aimed to understand TB-related stigma (perceived, enacted, and internalised) and possible interventions to reduce stigma in Puducherry and Tamil Nadu, India. We conducted 47 in-depth interviews with PLWATB and household members and eight focus group discussions: two each with PLWATB, their household members, healthcare workers, and key informants. We found varying TB-related knowledge: the vast majority of interview participants reported incorrect modes of transmission, although most were also aware that TB is curable. Participants reported high levels of perceived stigma, with nearly two-thirds of PLWATB choosing to hide their disease to avoid being stigmatised in their community. Participants supported interventions including celebrity advocacy and school-based programming to increase community knowledge and reduce enacted stigma as well as support groups and counselling to reduce internalised stigma in PLWATB. This study has the potential to inform future interventions to reduce TB-related stigma in India.